2005
DOI: 10.1007/s11240-004-6914-0
|View full text |Cite
|
Sign up to set email alerts
|

Proliferation and germination of somatic embryos from embryogenic suspension cultures in Ph?nix dactylifera

Abstract: The present study demonstrates a procedure for the rapid development of a high number of somatic embryos from embryogenic suspension culture. This method might be efficient for mass propagation of Phoenix dactylifera L. Embryogenic callus placed in liquid medium with 10 )5 M ABA yielded an average 72 embryos per 100 ml of culture medium within 2 months, while those placed on solid medium yielded an average of 33, 20 and 16 embryos per 100 ml of culture medium respectively for 10 )7 , 10 )6 and 10 )5 M ABA afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
30
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 28 publications
3
30
1
Order By: Relevance
“…The somatic embryos were formed within 3-6 weeks after inoculation in the liquid media (Figures 5b, 7b) while they were formed in 12-18 weeks on solid medium (Ibraheem et al, 2010). Similar to our results Zouine et al (2005) reported that the initiation of somatic embryos in suspension culture within 2 months, while on solid medium somatic embryos were formed after 4 months. Recently, AlKhayri (2012) found that cell suspensions accelerated significantly the appearance of somatic embryos in date palm cv.…”
Section: Callus Induced From Shoot Tipssupporting
confidence: 90%
See 4 more Smart Citations
“…The somatic embryos were formed within 3-6 weeks after inoculation in the liquid media (Figures 5b, 7b) while they were formed in 12-18 weeks on solid medium (Ibraheem et al, 2010). Similar to our results Zouine et al (2005) reported that the initiation of somatic embryos in suspension culture within 2 months, while on solid medium somatic embryos were formed after 4 months. Recently, AlKhayri (2012) found that cell suspensions accelerated significantly the appearance of somatic embryos in date palm cv.…”
Section: Callus Induced From Shoot Tipssupporting
confidence: 90%
“…Khalas suspension cultures after adding BAP at 1 mg l -1 to the medium enriched with 2,4-D. Adding BAP to date palm suspension cultures was also reported by Zouine et al (2005) and Zouine and El Hadrami (2007). For other species, Yamamoto and Yamada (1986) reported that the hormonal combination of NAA and BA was the most suitable for cell suspension culture for snakeroot (Rauwolfia serpentine).…”
Section: Callus Induced From Shoot Tipsmentioning
confidence: 81%
See 3 more Smart Citations